Revolusi Mental di Indonesia Perspektif Al-Qur’an - Nur Yasin; Ihya Ulumudin (Moderasi : Journal of Islamic Studies, 2021)
Mental is a vital element of man who must always be kept in power. Mental positive must not be negative because if the negative will be negative throughout his body. In a leader country and people something inherently inseparable. Then both of them must have a mental that is equally positive and synergized to achieve a safe and prosperous country.